Endoscopic DCR with and without prolene stent in rural area: a prospective randomized study - Kumar, Abhay; Porwal, Prateek Kumar; Dubey, Kailash Prasad; Singh, Harshita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The objective of the study was to compare the results of endoscopic DCR with and without prolene stenting and to assess subjective and anatomical success in patients undergoing prolene stenting. Methods: The surgical outcomes of endoscopic endonasal DCR was compared in 100 patients of chronic dacryocystitis with nasolacrimal duct obstruction from June 2013 to May 2018. The successful outcome of surgery was defined by subjective improvement of symptoms and anatomical patency of the neo-ostium on syringing by nasal endoscopy. Results: In our study females were predominant in both groups with around 60% being females in group with stenting and 64% in group without stenting. Male to female ratio was 1:1.5 and 1:1.77 in group with stenting and without stenting. The symptomatic success rate of the surgery at the end of 3 months was 92% in group without stenting and 88% in group with stenting. There was no statistical difference in the results of two groups. Conclusions: We recommend that stenting is not routinely required for endoscopic DCR surgeries. A selective stenting approach may be advocated using prolene 3-0, using stenting for specific indications. With proper surgical technique and good follow up, endoscopic DCR without stenting is treatment of choice for chronic nasolacrimal duct obstruction.